Teaching Innovation Project: Formative and Shared Assessment in Education. Results of Knowledge Transfer between University and School - Cristina Pascual-Arias; Víctor M. López-Pastor; Carolina Hamodi Galán (Universidad Autónoma de Madrid, 2019)
In this work we present the development of the Teaching Innovation Project (TIP) "The Formative and shared assessment in education. Transfer of knowledge between University and School ", developed at the University of Valladolid, specifically in the Faculty of Education of Segovia. We have developed a case study analyzing the double way of knowledge transfer: from the university to the school and from the school to the university. To this end, two lines of intervention have been organized: (a) the development of Tutored Learning Projects, internship periods, Final Degree Projects, Master's Thesis and Doctoral Theses; (b) the development of an inter-classroom seminar on Formative and Shared Evaluation, as a permanent training activity for teachers in all stages of education, from early childhood education to university. We have obtained as a result advantages, disadvantages and proposals for improvement for later courses from the point of view of student learning, teacher teaching and the teaching and learning process itself.